Factor Xa inhibitors for preventing recurrent thrombosis in patients with antiphospholipid syndrome: a longitudinal cohort study. (November 2019) - Sato, T; Nakamura, H; Fujieda, Y; Ohnishi, N; Abe, N; Kono, M; Kato, M; Oku, K; Bohgaki, T; Amengual, O; Yasuda, S; Atsumi, T
Objective: The objective of this study was to clarify the efficacy and safety of factor Xa inhibitors for antiphospholipid syndrome patients in real world utilization. Methods: This is a retrospective cohort study comprised of all consecutive patients with antiphospholipid syndrome in our department over a period of 28 years. Patients treated with factor Xa inhibitors were extracted from the cohort. As a control group, patients treated with warfarin were selected from the same cohort with matched age, gender, coexistence of systemic lupus erythematosus, and the presence of antiplatelet therapy, after which we used a propensity score for each of the risk factors as an additional covariate in multivariate Cox proportional hazard regression. The primary endpoint was set as thrombotic and hemorrhagic event-free survival for five years. Results: Among 206 patients with antiphospholipid syndrome, 18 had a history of anti-Xa therapy (five rivaroxaban, 12 edoxaban, one apixaban). Fourteen out of 18 patients on anti-Xa therapy had switched to factor Xa inhibitors from warfarin. Event-free survival was significantly shorter during anti-Xa therapy than that during warfarin therapy (hazard ratio: 12.1, 95% confidence interval: 1.73–248, p = 0.01) (Figure 1(a) ). Similarly, event-free survival in patients treated with factor Xa inhibitors was significantly shorter compared with controls (hazard ratio: 4.62, 95% confidence interval: 1.54–13.6, p = 0.0075). In the multivariate Cox proportional hazard model, event-free survival in patients with anti-Xa therapy remained significantly shorter (hazard ratio: 11.9, 95% confidence interval: 2.93–56.0, p = 0.0005). Conclusions: Factor Xa inhibitors may not be recommended for antiphospholipid syndrome.